Epistemological Integration and Physical Education Practice from a Hadith Perspective: A Comprehensive Analysis - Maslani Maslani; Taupik Hamdani; Bilal Zakawali Al-Fathoni (AIM: Journal of Islamic Education Management, 2026)
In practice, physical education often suffers from secular reductionism, narrowly understood as the mechanization of physical activity without the intimacy of moral and spiritual values due to the influence of philosophical dualism. In response to this paradigmatic anomaly, Islam offers a holistic philosophical construction that views the body as an imperative trust from Allah SWT that must be maintained and optimized to support the mission of worship and vicegerency. This study aimed to dismantle, reconstruct, and comprehensively examine the concept of physical education from the epistemological perspective of hadith while evaluating its applied relevance in contemporary educational curricula. Using a qualitative method through library research, this study descriptively and argumentatively dissects primary and secondary sources. The results show that the prophetic Sunnah functionally classifies physical activities into cardiovascular endurance instruments (such as running and swimming) and cognitive and concentration instruments (such as archery and horseback riding). All these practices must be supported by a foundation for nutritional management and sanitation. Through the ma'anil hadith approach, the concept of a “strong believer” is proven to refer not merely to muscular brutality, but to a synergistic combination of depth of faith and readiness for physical mobility. In conclusion, the physical education curriculum must submit to the Islamic prophetic blueprint to transform mechanical movements into a fundamental method for holistic moral character building.